Understanding the science of resistance training: An evolutionary perspective - Kraemer, W. J.; Ratamess, N. A.; Flanagan, S. D.; Shurley, J. P.; Todd, J. S.; Todd, T. C. (Sports Medicine, 2017)
The history of resistance training research began with anecdotal ideas and a slow growth of research from the late 1890s through the 1970s. The mid-1970s were a nexus point when resistance training studies evolved from just strength assessments to importance in physiological systems, physical health, and physical performance capabilities for individuals interested in physical fitness through to those seeking elite athletic performances. The pursuit of understanding program design and what mediated successful programs continues today as new findings, replication of old concepts, and new visions with the latest technologies fuel both our understanding and interest in this modality. This brief review highlights some of the important scientific contributions to the evolution of our scientific study of resistance training and provides a literature base analysis for greater quantification of the origins and expanse of such investigations.